Edukasi Dan Simulasi Produksi Minyak Gosok Rumahan Pada Masyarakat Kelurahan Lok Bahu, Kecamatan Sungai Kunjang, Kota Samarinda - Chaidir Masyhuri Majiding; Risna Agustina; Wisnu Cahyo Prabowo; Abdul Rahim; Mahfuzun Bone; Azhar (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Maintaining health is an obligation and an important investment in order to live a productive and meaningful life. To maintaining and improving health, various health methods and products have attracted public attention. One product that is getting more attention is rubbing oil. The aim of this activity is to provide knowledge and skills to the community of Lok Bahu Region in producing rubbing oil independently. An educational approach is used to explain the ingredients, manufacturing process, and benefits of using the rubbing oil. The results of this service activity show a significant increase in public knowledge about the health benefits of using rubbing oil. Apart from that, service participants also demonstrated increased skills in making rubbing oil which can be implemented independently in the household environment. Evaluation of this activity shows that this program has succeeded in increasing public awareness of the use of natural ingredients for health.